SCProcessor Builder: A Tool to Create and Simulate Processors in SystemC - Melo, Julio; Leite, Luiz C.; Silveira, Max M.; Junior, Rivaldo; Kreutz, Marcio (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2012)
This paper presents the SCProcessor Builder that consists on a toolset that enables the modeling and simulation of different processor architecture and behavior. The models are designed using XML language and state machines for the structural and behavior parts respectively. The proposed tool converts the models to SystemC in order to simulate the execution of programs on modeled processors.